Open hydatid liver cysts in the bile ducts: cystobiliary disconnection due to transhepaticocystic choledocostomy - Perdomo, Roberto; Balboa, Oscar; Morelli, Raúl; Melognio, Silvio (Cirugía del Uruguay, 1976)
The authors analyze the post-operatory problems of patients who were treated for hydatic cysts open and evacuated in the common hile duct when the residual adventicial cavity maintains a wide canalicular communication, which is not totally solved by bipolar evacuation. They present a method of cysto-biliary disconection by trans-hepato-cystic choledocostomy with a T- tube, and they present three cases which show its practica! aplication. The technical details are described, and sone variations in the indication, theoretically also apt for this procedure, are also studied.